'Struggling with the word strange my hands have been burned many times': mapping a migratory research aesthetics in arts-based strangeness research. Issue 1 (2nd January 2018) - Frimberger, Katja
Abstract: The following paper maps a migratory research aesthetic within four arts-based research workshops, which explored international students' intercultural 'strangeness' experiences. Using a neo-materialist framing, the article argues that an emphasis on social-aesthetic-material 'production' in arts-based research allows for a rhizomatic knowledge topography that accounts for the materially entangled nature of intercultural experience and prioritises relationship-building, collective learning experiences and aesthetic experimentation over the researcher's epistemological mastery. The article maps a migratory research aesthetic by interweaving workshop vignettes, image and audio-based data examples into theoretical reflections. By focusing on the translation of intercultural experience into the different aesthetic workshop modalities – from creative writing, to performative reading and problem-focused discussion, the paper shows that a rhizomatic knowledge production in arts-based research necessarily oscillates: between semiotic and embodied modalities, individual and collective experience, as well as between 'real' and 'fictional' modes of philosophising. Whatever the movement of 'translation' however, these acts of aesthetic making and philosophising around intercultural 'strangeness' are always embedded in the wider map of human and non-human interactions in the world.